2023
DOI: 10.1186/s42466-023-00273-5
|View full text |Cite
|
Sign up to set email alerts
|

Resting state EEG as biomarker of cognitive training and physical activity’s joint effect in Parkinson’s patients with mild cognitive impairment

Carlos Trenado,
Paula Trauberg,
Saskia Elben
et al.

Abstract: Background Cognitive decline is a major factor for the deterioration of the quality of life in patients suffering from Parkinson’s disease (PD). Recently, it was reported that cognitive training (CT) in PD patients with mild cognitive impairment (PD-MCI) led to an increase of physical activity (PA) accompanied by improved executive function (EF). Moreover, PA has been shown to alter positively brain function and cognitive abilities in PD. Both observations suggest an interaction between CT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Specifically, the rsEEG delta and theta rhythms were reduced in magnitude after the CCT program compared to the control Sham program. These findings extend recent evidence showing that a combined eight-week program with CCT and physical activity in a hospital setting induced beneficial effects on cognitive functions that (negatively) correlated with rsEEG theta rhythms [39].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, the rsEEG delta and theta rhythms were reduced in magnitude after the CCT program compared to the control Sham program. These findings extend recent evidence showing that a combined eight-week program with CCT and physical activity in a hospital setting induced beneficial effects on cognitive functions that (negatively) correlated with rsEEG theta rhythms [39].…”
Section: Discussionsupporting
confidence: 88%
“…They showed decreased activity of rsEEG delta, theta, and beta rhythms in older MCI patients and improved cognitive functions after a combined eight-week program with CCT and physical activity [38]. Along the same line, a recent study in PDCD patients showed that a combined eight-week program with CCT and physical activity in hospital settings induced beneficial effects of cognitive functions in negative correlation with rsEEG theta rhythms and positive correlation with rsEEG beta rhythms [39].…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, the lower EEG power level of the right hemisphere may be representative of lower attentional skill, as the result suggested that δ wave of bilateral parietal, β, γ waves of R-occipital lobe, θ wave of R-frontal, and especially α wave of bilateral frontal lobe were lower in the low-attention group. The role of θ and α power in frontal areas can be biomarkers for both cognitive and physical performances [ 29 ]. The frontal poles are brain regions that play a key role in emotional regulation and cognitive abilities [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These network changes were negatively correlated with cognitive function in early PD [ 304 ]. A significant joint effect of interventions on EF and task-based changes for the negative correlation between attention and θ power, a positive correlation between EF and α power, and a significant negative relationship between attention and θ power were found over time [ 305 ]. Cognitive deficits were further underlined by alterations at the brain network level, including higher δ and θ activity, lower α and β activity, increased connectivity, and segregated network organization [ 306 ].…”
Section: Neurophysiological Studies In Pd-cimentioning
confidence: 99%